What I eat : around the world in 80 diets - Menzel, Peter, 1948- (Material World Books ; Ten Speed Press, 2010)
Photographs and text examine the diets of eighty individuals who live in different places throughout the world, including an Egyptian camel broker, a Japanese sumo wrestler, a Sudanese refugee in Chad, an Arctic hunter, a Namibian diamond polisher, and a wounded Iraq war veteran.